Обыкновенная история: роман в 2 частях / [иллюстрации Ю. Гершковича] - Гончаров Иван Александрович (1981)
Экземпляры: ф. 4 (20210304) / Инвентарный номер: 113557 / Цена: 10.00 / Авт.знак: Г 65 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)1